Modelo de desarrollo organizacional hotelero para crear estrategias de desarrollo local en la hostería Rumipamba de las rosas. - Jiménez Trujillo, Andrea Vanessa (2020)
The thesis project was developed in order to elaborate a hotel organizational model that promotes community tourism and to link it in the Patain community. Salcedo canton located in the Cotopaxi province, since it is not a well known place, for this reason it needs to elaborate a local development strategy that promotes community tourism by identifying tourist attractions, The information was gathered from different texts, web pages, information from the GAD parish and the MINTUR collaboration. The first step was to find out about the interest of the hostel and the community in the development of tourist activity in the area through the application of surveys in the main organizations. At the same time, the tourist design route was socialized and confirming its feasibility. The purpose of this study is to increase the influx of tourists and provide new alternatives for local development by generating new sources of employment, increasing in cash flow, publicizing its attractions and highlighting the culture. The study consists of five chapters which detail the development of a proposal for the design of a tourist route in the Patain town located in the Salcedo canton, Cotopaxi province by applying this proposal.